Physiological characteristics of Indonesian junior badminton players: Men's double category - Apriantono, T.; Herman, I.; Winata, B.; Ikhwan Hidayat, I.; Fahmi Hasan, M.; Dwi Juniarsyah, A.; Indah Ihsani, S. (International Journal of Human Movement and Sports Sciences, 2020)
The primary aim of this study is to assess the VO2max and anthropometric characteristics of men's double category; Next is to analyze match characteristics of men's double category; and finally, to compare the heart rate (HR) and blood lactate concentration calculated on-court with that obtained under laboratory conditions during an incremental test. 12 junior badminton players from Jaya Raya Badminton Club were enrolled as the subjects for this study. All participants were partnered up in 6 pairs (pair 1 to pair 6). During the first session (laboratory condition), VO2max was measured by using a velocity dependent ramp test (INCS) based on incremental protocols. During the second session (on-court condition), the participants played a simulated match on court. A total of 350 rallies were analyzed. Statistical analyses revealed that double junior men's players hit the shuttlecock more often using drive shots techniques (466 shots). The ANOVA revealed significant differences regarding fB between pair 3 vs pair 6 (p=0.004), pair 4 vs pair 6 (p=0.030), and pair 5 vs pair 6 (p=0.023). For the lactate measures, ANOVA revealed significant main effects of time (p=0.001) and group (p=0.001). Furthermore, the significance of HR average among laboratory and on-court conditions was established with the help of an independent t-test. The study demonstrated that the physiological characteristics of Indonesian men's double category are intermittent activities of high and low intensities, interspersed by short recovery periods. It was also discovered that the adrenergic strategy results in enhanced HR and lactate levels in the laboratory than on-court conditions.